Development and evaluation of BCI for operating VR flight simulator based on desktop VR equipment. (January 2022) - Zhou, Zhengdong; Zhang, Lingwei; Wei, Shisong; Zhang, Xuling; Mao, Ling
Abstract: Advancement of brain-computer interface (BCI) has shown its applications in various scenarios, including flight control. Flight simulator is a crucial part for aircraft design or experiment. Desktop virtual reality (VR)-based flight is a perfect choice for overcoming existing problems in head-mounted VR flight simulations, such as dizziness and isolation, which make interaction and sharing very difficult. In this paper, a BCI based on the steady-state visual evoked potential paradigm and a VR flight simulator were developed and integrated. The performance of the developed system was evaluated quantitatively for comparative studies. Experimental results show that the developed system is very convenient and suitable for VR flight simulations. The average operating accuracies with plane and VR visual stimuli are 81.6% and 86.8%, respectively. The VR visual stimuli can improve the average operating accuracy by 5.2% compared with the plane visual stimuli.